Drosophila Food-Associated Pheromones: Effect of Experience, Genotype and Antibiotics on Larval Behavior. - Julien Thibert; Jean-Pierre Farine; Jérôme Cortot; Jean-François Ferveur (PLoS ONE, 2016)
Animals ubiquitously use chemical signals to communicate many aspects of their social life. These chemical signals often consist of environmental cues mixed with species-specific signals-pheromones-emitted by conspecifics. During their life, insects can use pheromones to aggregate, disperse, choose a mate, or find the most suitable food source on which to lay eggs. Before pupariation, larvae of several Drosophila species migrate to food sources depending on their composition and the presence of pheromones. Some pheromones derive from microbiota gut activity and these food-associated cues can enhance larval attraction or repulsion. To explore the mechanisms underlying the preference (attraction/repulsion) to these cues and clarify their effect, we manipulated factors potentially involved in larval response. In particular, we found that the (i) early exposure to conspecifics, (ii) genotype, and (iii) antibiotic treatment changed D. melanogaster larval behavior. Generally, larvae-tested either individually or in groups-strongly avoided food processed by other larvae. Compared to previous reports on larval attractive pheromones, our data suggest that such attractive effects are largely masked by food-associated compounds eliciting larval aversion. The antagonistic effect of attractive vs. aversive compounds could modulate larval choice of a pupariation site and impact the dispersion of individuals in nature.